Learning Models in Mathematics and Science Education to Improve High Order Thinking Skill (HOTS): A Systematic Literature Review - Muthmainnah, Muthmainnah; Munzil, Munzil; Habiddin, Habiddin; Rahayu, Sri (JURNAL PENDIDIKAN SAINS (JPS), 2025)
This systematic literature review examines learning models in mathematics and science education that improve Higher-Order Thinking Skills (HOTS). The review focuses on studies from 2000 to 2023, addressing Indonesia's need to enhance HOTS in response to low performance in global assessments like PISA. Using the PRISMA method, 20 studies were analyzed based on criteria such as HOTS focus and relevance to primary and secondary education. Findings reveal that Inquiry-Based Learning (IBL) is the most commonly used model across disciplines, promoting critical thinking and problem-solving. Problem-Based Learning (PBL) is also widely applied, particularly in senior high schools, encouraging creativity through real-world problems. Discovery Learning, though less frequent, is effective in fostering independent inquiry in chemistry education. The study concludes that inquiry-driven and problem-solving models are key to developing HOTS, especially in secondary education, where cognitive demands increase. These models should be integrated into curricula to meet the challenges of the Fourth Industrial Revolution.